PROFESSIONAL QUALITY AND PROFESSIONAL COMPONENT RATIO (TAMADDUN NURI JURNALI, 2024)
In this article, it is stated that a pedagogue is a person responsible for the education and upbringing of his specialty before the society, at the same time, he must regularly improve his professional training, teacher, teacher, teacher, educator. , to have the right to be a pedagogue, to be more precise, to be the owner of professional competence, the ways to become a mature specialist are explained. Also, information is given about the psychological foundations of professional development, and the general role and function of psychology in the development of the individual is also widely covered. The psychological content of professional development is analyzed on the basis of military psychology.